The Diversity of Participants in Environmental Citizen Science. (19th March 2021) - Pateman, Rachel; Dyke, Alison; West, Sarah
Reported benefits of environmental citizen science include the collection of large volumes of data, knowledge and skills gained by participants, local action, and policy influence. However, it is unclear how diverse citizen science participants are, raising concerns about representativeness of data and whether individual, societal, and environmental benefits are evenly distributed. We surveyed 8, 220 people representing a cross section of the population in Great Britain to ask whether they had participated in environmental citizen science, allowing us to examine who is and who is not participating. Using logistic regression, we examined relationships between demographic variables, and crucially the interactions between these variables, and the likelihood of participation and whether participation was repeated. Men were more likely to participate than women. People identifying as from white ethnic groups were more likely to participate than those identifying as from minority ethnic groups; participation by women from minority ethnic groups was particularly low. Participation by those from white ethnic groups declined with socio-economic status, but this was not the case for those from minority ethnic groups. Participation was highest amongst those in education (studying at school, college, or university) and lowest amongst the unemployed. We recommend citizen science practitioners carefully consider the aims of projects and thus the diversity of participants they wish to attract. We discuss potential mechanisms for widening participation, for example, engaging participants through third parties already embedded in communities and providing a variety of tasks for people with different amounts of time and types of skills to offer. Finally, we encourage practitioners to document and publish participant demographics to monitor diversity in citizen science.